Friendship or vicarious relationship? Exploring the intricacies faced by basic sciences in integrated curricula - Dinesh Kumar; Aneesh Basheer (Tabriz University of Medical Sciences, 2019)
In response to the evolving needs and reports on medical education, many medical schools have been pursuing curricular integration. Contrary to Abraham Flexner who persuaded that teaching of medical sciences, from basic to clinical, should be a critical component of the discipline based curriculum, 'integration', in its purest sense unifies separate areas of knowledge which quenches the needs of adult learners. However, most medical schools struggle with integrating their curricula owing to the confusion derived from diverse definitions and multiple learning theories. A common criticism of integrated curriculum is that students will not see the relevance of basic sciences and this significantly minimizes the role of basic sciences in medical education. The crux of integration is achieving the balance of clinical and basic sciences in a manner that best serves the student to maximize student engagement and knowledge retention. In this paper, we made an attempt to address the contextual issues existing in medical schools, the changing role of basic sciences in present day medical education and the optimal strategy to achieve effective integration of basic sciences. We propose that a dynamic interconnectedness happening at various levels is more important to achieve effective integration rather than mere deliberate unification of individual disciplines.